2022
DOI: 10.1155/2022/5812627
|View full text |Cite
|
Sign up to set email alerts
|

Dental Undergraduates and Interns’ Awareness, Attitudes, and Perception of Radiological Protection

Abstract: Medical ionizing radiation is widely used in hospitals, in particular dental clinics, and in medical research to facilitate the diagnosis and treatment of patients. The awareness, attitude, and perception of ionizing radiation exposure among dental undergraduate students and interns in radiological investigations and dental care clinics were investigated. A cross-sectional study was conducted; 17 questions were designed online using the software “QuestionPro,” which was licensed to the University of Imam Abdul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…Study results revealed that most dentists were aware of radiation hazards and protection. 1,2 Our results are comparable to studies conducted previously like a study done in 2020 by Khamtuikrua C, et al, 3 and Mahasneh AM, et al, 4 in the year 2022. Dental radiography is considered safe during pregnancy if protective measures have been provided such as thyroid collar, Lead apron, and use of highspeed E films.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Study results revealed that most dentists were aware of radiation hazards and protection. 1,2 Our results are comparable to studies conducted previously like a study done in 2020 by Khamtuikrua C, et al, 3 and Mahasneh AM, et al, 4 in the year 2022. Dental radiography is considered safe during pregnancy if protective measures have been provided such as thyroid collar, Lead apron, and use of highspeed E films.…”
Section: Discussionsupporting
confidence: 90%
“…Dental radiographs, commonly called X-rays, are used to diagnose hidden dental problems or diseases. 1 These include malignant and benign lesions, bone loss, bony deformities, cavities, skeletal anomalies, impactions, etc. It is a great diagnostic tool that helps the dentist see any damage or disease that is not visible to the naked eye.…”
Section: Introductionmentioning
confidence: 99%